Investigation of the Antioxidant, Antimicrobial, and Cytotoxic Activities of Endemic Marrubium rotundifolium Boiss - Aydın Köse, Fadime; Öztürk, İsmail; Cin, Seden; Baykan, Şura (European Journal of Therapeutics, 2023)
Objective: Marrubium L. genus (Lamiaceae), which has 40 taxa in the world, is represented by 25 taxa in Turkey. Marrubium rotundifolium Boiss. is an endemic species and is distributed in Aegean. This study was aimed to determine the antioxidant, antimicrobial, and cytotoxic effects of hexane, ethyl acetate, and methanol extracts of the endemic Marrubium rotundifolium Boiss. Methods: Ultrasonic-assisted extraction was applied to aerial parts of the plant. The Folin-Ciocalteu and aluminum chloride/ potassium acetate methods determine the extract’s total phenolic and flavonoid contents. The 2,2’-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS+) radical decolorinaztion assay was used to determine the extracts’ Trolox equivalent antioxidant capacity. The deoxyribose assay was carried out for determining the extracts’ OH− radical scavenging activity, and 2,2-diphenyl1-picrylhydrazyl was used for radical scavenging assay. 3-[4,5-Dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide method was used to determine the in vitro cytotoxicity of plant extracts on 3 cancer (Caco-2, SH-SY5Y, and PC-3) and 2 non-cancer cell lines (NIH-3T3 and HK-2). The antimicrobial activity was examined through the microdilution method. Results: Phenolic contents of 2.62 ± 0.16 gallic acid equivalents μg/mL were observed in the methanol extract, while the highest flavonoid content was determined in n-hexane extract (168.63 ± 2.76 QE μg/mL). In the OH˙−, ABTS˙+, and 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity studies, M. rotundifolium methanol extract showed higher IC50 values at lower doses (0.277 ± 0.024, 3.21 ± 0.081, 0.033 ± 0.001 mg/mL, respectively). Concerning the cytotoxic activity, only methanol extract showed inhibition on PC-3 cells (IC50: 0.173 ± 0.018 µg/mL). Minimum inhibitory concentrations of the extracts against Gram-positive bacteria were lower than Gram-negative bacteria and yeast strains. Conclusion: This study is the first detailed study that examines antioxidant and cytotoxic properties of endemic M. rotundifolium.